A CRISPR/Cas12a-empowered surface plasmon resonance platform for rapid and specific diagnosis of the Omicron variant of SARS-CoV-2. Issue 8 (3rd June 2022) - Chen, Zhi; Li, Jingfeng; Li, Tianzhong; Fan, Taojian; Meng, Changle; Li, Chaozhou; Kang, Jianlong; Chai, Luxiao; Hao, Yabin; Tang, Yuxuan; Al-Hartomy, Omar A; Wageh, Swelm; et al.
Abstract: The outbreak of the COVID-19 pandemic was partially due to the challenge of identifying asymptomatic and presymptomatic carriers of the virus, and thus highlights a strong motivation for diagnostics with high sensitivity that can be rapidly deployed. On the other hand, several concerning SARS-CoV-2 variants, including Omicron, are required to be identified as soon as the samples are identified as 'positive'. Unfortunately, a traditional PCR test does not allow their specific identification. Herein, for the first time, we have developed MOPCS (Methodologies of Photonic CRISPR Sensing), which combines an optical sensing technology-surface plasmon resonance (SPR) with the 'gene scissors' clustered regularly interspaced short palindromic repeat (CRISPR) technique to achieve both high sensitivity and specificity when it comes to measurement of viral variants. MOPCS is a low-cost, CRISPR/Cas12a-system-empowered SPR gene-detecting platform that can analyze viral RNA, without the need for amplification, within 38 min from sample input to results output, and achieve a limit of detection of 15 fM. MOPCS achieves a highly sensitive analysis of SARS-CoV-2, and mutations appear in variants B.1.617.2 (Delta), B.1.1.529 (Omicron) and BA.1 (a subtype of Omicron). This platform was also used to analyze some recently collected patient samples from a local outbreak in China, identified by the Centers for Disease Control and Prevention. This innovative CRISPR-empowered SPR platform will further contribute to the fast, sensitive and accurate detection of target nucleic acid sequences with single-base mutations. Abstract : This paper presents an unprecedented SARS-CoV-2 variants gene detection platform MOPCS(Methodologies of Photonic CRISPR Sensing), which achieved high specificity and sensitivity at the same time by the innovative crossover of the unique sequence-specific recognizing ability of the CRISPR/Cas system and the superior sensitivity of the surface plasmon resonance sensing technique.